Reading experience drives L2 reading speed development: a longitudinal study of EAL reading habits - Schmidtke, Daniel; Rahmanian, Sadaf; Moro, Anna L. (Frontiers in Education, 2024)
The present longitudinal study examined the development of text processing speed in a sample of 142 L1 Cantonese or Mandarin English learners enrolled in an eight-month university bridging program. The study tested the hypotheses that (i) learners become faster readers after intensive English language instruction, and that (ii) learners who read more English texts tend to make larger gains in reading speed. Participants completed a reading habits log each week, reporting information about their reading activity, including the type of texts they read, the amount of time they spent reading each text, and the number of pages they read.Results revealed that English language learners spent less time reading per page of text by program end, showing a significant linear weekly increase in reading speed. Moreover, there was a significant effect of reading experience: learners who read more pages of text than their peers by the end of the bridging program also tended to make the largest net gains in reading speed. The results support the idea that reading experience is a factor that contributes to reading speed development in English language learners.